Mapping Research on the Influence of Social Media on Consumer Food Behavior a Bibliometric Approach - Lau, Elfreda Aplonia; Rukmana, Arief Yanto; Uhai, Sabalius; Mokodenseho, Sabil; Tapaningsih, Weni Indah Doktri Agus (The Eastasouth Journal of Social Science and Humanities, 2024)
This study conducts a bibliometric analysis to systematically map the research landscape on the influence of social media on consumer food behavior. The analysis encompasses 1000 scholarly articles published between 1962 and 2024, accumulating 32,394 citations over 62 citation years. Through co-citation and bibliographic coupling analyses, key clusters and trends are identified, revealing the multifaceted nature of social media's impact on food-related attitudes and behaviors. Insights from the analysis offer practical implications for marketers, policymakers, and researchers, guiding strategic decision-making in areas such as marketing communication, public health interventions, and interdisciplinary collaboration. The findings underscore the importance of continued research efforts to address emerging gaps and deepen our understanding of the evolving dynamics between social media and consumer food behavior.